Inflammatory Effects of Subacute Exposure of Roundup in Rat Liver and Adipose Tissue. Issue 2 (23rd May 2019) - Pandey, Aparamita; Dhabade, Prachi; Kumarasamy, Anand
Roundup is a popular herbicide containing glyphosate as an active ingredient. The formulation of Roundup is speculated to have critical toxic effects, one among which is chronic inflammation. The present study analyzed adverse inflammatory effects in the liver and adipose tissue of rats after a subacute exposure of Roundup. Adult male rats were exposed to various doses of Roundup (0, 5, 10, 25, 50, 100 and 250 mg/kg bodyweight [bw] glyphosate) orally, everyday for 14 days. On day 15, liver and adipose tissues from dosed rats were analyzed for inflammation markers. C-reactive protein in liver, cytokines IL-1β, TNF-α, IL-6, and inflammatory response marker, and prostaglandin–endoperoxide synthase were upregulated in liver and adipose of rats exposed to higher (100 and 250 mg/kg bw/d) doses of Roundup. Cumulatively, our data suggest development of inflammation in lipid and hepatic organs upon exposure to Roundup. Furthermore, liver histological studies showed formation of vacuoles, fibroid tissue, and glycogen depletion in the groups treated with doses of higher Roundup. These observations suggest progression of fatty liver disease in Roundup-treated adult rats. In summary, our data suggest progression of multiorgan inflammation, liver scarring, and dysfunction post short-term exposure of Roundup in adult male rats.